2003
DOI: 10.1023/b:catl.0000004121.26500.ee
|View full text |Cite
|
Sign up to set email alerts
|

Probing Active Sites During Palladium-Catalyzed Alcohol Oxidation in “Supercritical” Carbon Dioxide

Abstract: Structural information has been gained during aerobic benzyl alcohol oxidation in ''supercritical'' carbon dioxide at 150 bar on alumina-supported palladium by X-ray absorption spectroscopy while monitoring simultaneously the performance of the catalyst. The reduction of the catalyst by benzyl alcohol could be monitored by the analysis of the near-edge region of the Pd K-edge. The palladium constituent was mainly in metallic state under operating conditions. Partial reoxidation was observed when only oxygen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 57 publications
2
35
1
Order By: Relevance
“…95%) could be achieved [23]. The phase behaviour of the reaction mixture [25,27] and the oxidation state of the solid catalyst [28,29] were found to be crucial for the high catalytic activity. In particular, we showed that the reaction could be effectively investigated, understood and optimized only by applying the appropriate in situ spectroscopic techniques (combined transmission IR/ATR-IR and X-ray absorption spectroscopy).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…95%) could be achieved [23]. The phase behaviour of the reaction mixture [25,27] and the oxidation state of the solid catalyst [28,29] were found to be crucial for the high catalytic activity. In particular, we showed that the reaction could be effectively investigated, understood and optimized only by applying the appropriate in situ spectroscopic techniques (combined transmission IR/ATR-IR and X-ray absorption spectroscopy).…”
Section: Introductionmentioning
confidence: 94%
“…Section 2 and Refs. [28,29]). During the experiments with the palladium catalyst the reaction rate measured in the in situ XAS flow cell was 1890 mol product mol Pd À1 h À1 (80 8C, 150 bar, 1.9 mol% alcohol, 1.9 mol% O 2 0.1 mol/min CO 2 ).…”
Section: Operando Xas Investigations During Aerobic Benzyl Alcohol Oxmentioning
confidence: 99%
“…In order to obtain operando structural analysis by X-ray absorption spectroscopy (XAS), the standard reactor design of the Baiker group (Scheme 10) was adapted for analytical applications (Fig. 2a) [88,89,96].…”
Section: Heterogeneous Catalysis In Supercritical Comentioning
confidence: 99%
“…The results of some electrochemical [98,99] and EXAFS [100] studies have indicated a considerable oxygen coverage of the metal surface during alcohol oxidation. A feasible interpretation of this would be that oxygen interacts directly with the adsorbed alcohol (or alcoholate) in the rate-determining step, and this model is supported also by numerous kinetic studies [101,102].…”
Section: Zeolitesmentioning
confidence: 99%